Peningkatan Daya Saing melalui Pelatihan Penyusunan Laporan Keuangan Sederhana pada Jaringan Wirausaha (Jawara) Bojongsari - Dian Widiyati; Neneng Hasanah; Napisah Napisah (Penerbit Goodwood, 2022)
Purpose: One of the obstacles to obtaining additional capital is the inability to compile financial statements which is a condition for obtaining access to capital from banks. Many MSME players manage their business without having a basic knowledge or skills about good strategies. MSME actors need to be fostered and accompanied in the preparation of financial statements. So that they can compile financial statements in accordance with applicable standards. MSMEs can communicate their business to stakeholders, not only with regard to products, but also performance reflected in financial statements. MSMEs need to gain knowledge about adequate financial bookkeeping so that business expenses and income can be monitored accurately. Method: This activity is carried out in the form of training delivered by several methods such as lectures, discussions and mentoring. Result: The main target of this activity is MSME actors in Bojongsari, Depok. After the activity, participants are motivated and eager to get used to recording transactions. By getting used to recording transactions starting from the smallest thing, financial statements can be easily made with proof of transactions and regular recording. On this occasion, not only providing material to MSME actors, but also providing motivation and easy tips for compiling financial reports. Conclusion: MSME participants practice the knowledge gained, namely by getting used to recording every transaction that occurs in business, it is hoped that MSME actors can easily compile simple financial reports